Ashland, Cash City, and Sitka, Clark County - York, Adam (Kansas State University, The Chapman Center for Rural Studies, 2012)
This study discusses the relationship of early communities of Clark County, Kansas. The author uses various sources to weave together a narrative of communal interconnections and relationships in reference to the overarching landscape of the region. The communities discussed are Cash City, Ashland, and Sitka.
Adam York, “Ashland, Cash City, and Sitka, Clark County,” Chapman Center Research Collections,https://ccrsresearchcollections.omeka.net/items/show/101..
Keywords: Ashland; Sitka; Cimarron River; Clark County; Boot Hill; Atchison Topeka and Santa Fe Railroad